Mechanical and Microstructural Characterization of Single and Double Pass Aluminum AA6061 Friction Stir Weld Joints - Nurul Hidayah, Othman; L. H., Shah; M., Ishak (IOP Publishing, 2015)
This study focuses on the effect of single pass (SP), double sided pass (DSP) and normal double pass (NDP) method on friction stir welding of aluminum AA6061. Two pieces of AA6061 alloy with thickness of 6 mm were friction stir welded by using conventional milling machine. The rotational speeds that were used in this study were 800 rpm, 1000 rpm and 1200 rpm, respectively. The welding speed is fixed to 100 mm/min. Microstructure observation of welded area was studied by using optical microscope. Tensile test and Vickers hardness test were used to evaluate the mechanical properties of this specimen. Mechanical property analysis results indicate that at low rotational speeds, defects such as surface lack of fill and tunneling in the welded area can be observed. Vickers hardness of specimens however did not vary much when rotational speed is varied. Welded specimens using single pass method shows higher tensile strength and hardness value compared to both double pass methods up to 180.61 MPa. Moreover, DSP showed better tensile test and hardness test compared to NDP method. The optimum parameters were found to be single pass method with 1200 rpm of rotational speed. Therefore economically sound to only perform SP method to obtain maximum tensile strength for AA6061 FSW with thickness of 6 mm.